Pendidikan ketika Pandemi Covid-19 di Desa Rejosari, Grobogan, Jawa Tengah - Riky Fajar Sujatmiko; Wike Anggraini (Civitas Consecratio: Journal of Community Service and Empowerment, 2021)
The online learning policy is one way of Indonesian government strategies to continue on providing education for students and reducing the risk of spread of Covid-19. However, teachers, students, and parents find it difficult to implement this policy. The purpose of this community service activity is to increase public awareness on the importance of education, despite some limitations due to this pandemic, thus the learning enthusiasm should be maintained. This community service activity was carried out with a online learning socialization method. There were three groups, which consist of the children, the youth, and the elderly group. In the implementation process for groups of children, they tend to feel more comfortable in learning face to face. Then the author makes a quiz competition through the quizizz.com platform, and they seemed motivated to use smartphones in the learning process. For the youth group, the author conveyed the socialization of the Youth Information and Counseling Center activities in the Plosonambangan Village. Socialization in the adult group was carried out at the Rejosari Village Hall with female participants. The socialization activity went smoothly and successfully, which was marked by the participants’ interest when they heard the presentation of the socialization, enthusiasm in asking questions and the results of the survey through the Google Form.